A Single-Carbon Stable Isotope Ratio Model Prediction Equation Can Estimate Self-Reported Added Sugars Intake in an Adult Population Living in Southwest Virginia - Valisa E. Hedrick (MDPI AG, 2021)
The δ13C value of blood is a novel proposed biomarker of added sugars (AS) intake. AS prediction equations using either a single- (δ13C) or dual-isotope model (δ13C and δ15N) were previously developed in an adult population with high AS intake living in southwest Virginia (reference group). The purpose of this investigation was to test the δ13C single- and δ13C and δ15N dual-isotope prediction equations for AS intake in adults with a lower mean AS intake and different demographic characteristics (test group). The blood samples for the reference (n = 257 for single-isotope, n = 115 for dual-isotope) and test groups (n = 56) were analyzed for δ13C and δ15N values using natural abundance stable isotope mass spectrometry and were compared to reported dietary AS intake. When the δ13C single-isotope equation was applied to the test group, predicted AS intake was not significantly different from reported AS intake (mean difference ± standard error = −3.6 ± 5.5 g, Z = −0.55, p = 0.51). When testing the dual-isotope equation, predicted AS was different from reported AS intake (mean difference ± SEM = 13.0 ± 5.4 g, Z = −2.95, p = 0.003). δ13C value was able to predict AS intake using a blood sample within this population subset. The single-isotope prediction equation may be an alternative method to assess AS intake and is more objective, cost-feasible, and efficient than traditional dietary assessment methods. However, more research is needed to assess this biomarker with rigorous study designs such as controlled feeding.